Women in Chinese potato cultivation in Tamil Nadu: A multidimensional analysis - Sheela Immanuel; D. Jaganathan; P. Prakash; R. Muthuraj (JOURNAL OF ROOT CROPS, 2025)
Abstract Women’s contribution in agriculture is witnessed throughout the globe and their participation is contributing for the growth and development of the economy either directly or indirectly. Women tend to participate in major agricultural activities such as transplanting, weeding, irrigation, harvesting and post harvest activities. Chinese potato is a minor tuber crop grown on a commercial scale mostly in Kerala and Tamil Nadu. Farmers along the belt of Tirunelveli and Tenkasi districts in Tamil Nadu are cultivatingChinese potato due to its high demand and adaptability to the local climatic conditions. Women also play an important role in Chinese potato cultivation and hence a multidimensional analysis was conducted in Tenkasi and Tirunelveli districts. Household survey was conducted using simple random sampling with the help of an interview schedule. The data collected were analysed using appropriate statistical tools. The study revealed that 30.30 percent of women had more than 20 years of experience in Chinese potato cultivation. Majority (87.88%) of the women cultivated Chinese potato in marginal farms of less than 2.5 acres. Majority of the women’s level of aspiration and innovativeness were medium with 72.73% and 63.64% respectively. The needs, preferences, opportunities and constraints of the farm women were assessed to formulate strategies and action plan to empower women in Chinese potato cultivation.